Impact of gas turbine flexibility improvements on combined cycle gas turbine performance. (5th May 2021) - Abudu, Kamal; Igie, Uyioghosa; Roumeliotis, Ioannis; Hamilton, Richard
Highlights: CCGT flexibility can be improved by airflow extraction and injection approaches. Flexibility upgrade is more optimistic for standalone gas turbine than in CCGT mode. CCGT minimum environmental load extension is 19% Plant ramp-up rate increase by 51% Gas turbine airflow injection adversely increases bottoming cycle steam conditions. Abstract: The improvement of gas turbines flexibility has been driven by more use of renewable sources of power due to environmental concerns. There are different approaches to improving gas turbine flexibility, and they have performance implications for the bottoming cycle in the combined cycle gas turbine (CCGT) operation. The CCGT configuration is favourable in generating more power output, due to the higher thermal efficiency that is key to the economic viability of electric utility companies. However, the flexibility benefits obtained in the gas turbine is often not translated to the overall CCGT operation. In this study, the flexibility improvements are the minimum environmental load (MEL) and ramp-up rates, that are facilitated by gas turbine compressor air extraction and injection, respectively. The bottoming cycle has been modelled in this study, based on the detailed cascade approach, also using the exhaust gas conditions of the topping cycle model from recent studies of gas turbine flexibility by the authors. At the design full load, the CCGT performance is verified and subsequent off-design cases from the gas turbine air extraction and injection simulations are replicated for the bottoming cycle. The MEL extension on the gas turbine that brings about a reduction in the engine power output results in a higher steam turbine power output due to higher exhaust gas temperature of the former. This curtails the extended MEL of the CCGT to 19% improvement, as opposed to 34% for the stand-alone gas turbine. For the CCGT ramp-up rate improvement with air injection, a 51% increase was attained. This is 3% points lower than the stand-alone gas turbine, arising from the lower steam turbine ramp-up rate. The study has shown that the flexibility improvements in the topping cycle also apply to the overall CCGT, despite constraints from the bottoming cycle.